Mechanical and adhesion properties of Al/AlN multilayered thin films - Lee, JH; Kim, WM; Lee, TS; Chung, MK; Cheong, BK; Kim, SG (ELSEVIER SCIENCE SA, 2000)
An investigation was conducted on the mechanical properties of compositionally modulated Al/AlN thin films deposited by r.f. magnetron sputtering on Si(100) substrates. The films were made to have modulation periods ranging from 40 to 200 nm. The volume fraction of Al was varied from 0.125 to 0.625 for films with the minimum modulation period of 40 nm, but it was set to 0.5 otherwise. Hardness and adhesion of the deposited films were examined by nanoindentation and scratch test method, respectively. Residual stress of monolithic Al and AW films with varying thickness and multilayered films was also measured by a conventional beam-bending technique. As compared with a monolithic AlN film, films of various modulation periods with the Al volume fraction of 0.5 were found to have lower hardness. On the other hand, high hardness comparable to and 12% higher than that of monolithic AN him was registered for films that have the modulation period of 40 nm and the Al volume fraction 0.125 and 0.25, respectively. Al the modulated films were found to have critical loads almost twice as high as that of a single AlN film, except the one with the lowest Al volume fraction. From the scratch test, a cohesive failure was observed for films with alternating layers in residual stress state of opposite signs whereas an adhesive failure was noticed otherwise. These observations indicate that a load-carrying capacity of a modulated film depends not only on the modulation period and individual layer thickness but on the residual stress states of alternating layers. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: HARDNESS; SUPERLATTICES; STRESS